Elastic and anelastic phenomena related to eddy currents in cubic Ni2MnGa. (1st April 2018) - Kustov, S.; Corró, M.-Ll.; Kaminskii, V.; Saren, A.; Sozinov, A.; Ullakko, K.
Abstract: We study temperature, magnetic field and strain amplitude dependences of the Young's modulus and ultrasonic absorption in the cubic phase of stoichiometric Ni2 MnGa single crystal, using longitudinal oscillations (90 kHz) along [100] direction. We show that the additional softening of the Young's modulus below the Curie temperature, usually considered as elastic premartensitic phenomenon, originates instead from conventional microeddy current relaxation associated with individual domain wall motion. In general, existing controversial experimentally observed damping and "elastic" softening behaviours are controlled by a combination of micro- and macroeddy current relaxations, operating at different spatial scales and over distinct frequency ranges. Graphical abstract: Schematic representation of the frequency dependence of macro- and microeddy current related damping, δ M and δ μ, and Δ E -effect, Δ E E M, and Δ E E μ, respectively, under different magnetic fields. Image 1